Implementasi Kebijakan Penanganan Stunting Di Kalimantan Timur (Studi Pada Dinas Kesehatan Provinsi Kalimantan Timur) - Kus Indarto; Santi Rande; Friska Prastya Harlis; Muhammad Haidil Rivaldiansyah; Syahnaz Fahriza (Sawala : Jurnal Administrasi Negara, 2024)
This research aims to analyze the implementation of stunting management policies in East Kalimantan (Study at the East Kalimantan Provincial Health Service). According to the 2021 and 2022 Indonesian Nutrition Status Survey (SSGI), the prevalence of stunting in East Kalimantan is still high with an increase of 1.1 percent from the initial figure of 22.8 percent to 23.9%. The method used is qualitative with a descriptive approach. Data was collected through in-depth interviews, observation and documentation studies. The results of the research show that the implementation of the Stunting Management Policy in East Kalimantan carried out by the East Kalimantan Provincial Health Service has overall been implemented well, although it has not yet run optimally. There are several related indicators as follows: communication in the implementation of stunting management policies in East Kalimantan as a whole at the East Kalimantan Provincial Health Service has not been implemented optimally. Resources are still inadequate. The overall disposition in implementing this policy, the implementation of commitment and integrity, can be said to be good because it was implemented according to what was expected. The bureaucratic structure as a whole is running well, with the implementation of stunting management policies already in place Standard Operating Procedure (SOP). Keyword : Policy Implementation, Stunting, East Kalimantan Province